Foraminiferal Biostratigraphy of the Caversham Formation and Its Implication for Stratigraphy and Sedimentation Study, Northeast Otago, New Zealand - Budianto Toha (Ikatan Ahli Geologi Indonesia, 2001)
Foraminifera play an important role in stratigraphy and sedimentation analysis of the Caversham Formation. Foraminiferal biostratigraphy has allowed definition of the stratigraphic relationship between three sections studied, i.e. Puketeraki, Karitane Peninsula, and Matanaka Farm respectively. Additionally, foraminiferal assemblages satisfactorily determined New Zealand Stages and Substages of the Otaian and Altonian Stages of the lower Miocene (Burdigalian) age, as well as the depositional environment. Paleoecology of some particular foraminifera (e.g. Globoquadrina dehiscens and Ehrenbergina marwicki) has been utilized successfully to examine the depositional process.